Revisión del género apterostigma mayr: (hymenoptera: formicidae) - Lattke, John E. (Arquivos de Zoologia, 1997)
The genus Apterostigma is revised and redefined based upon the workers; 47 species are recognized, of which 20 are new. Out of the previously recognized species 18 are redescribed, 7 are synonimized and 1 is revalidated. Nine nominal species are grouped into the pilosum complex. All available information on the genus is summarized; illustrations and a key for identifying the workers are included.